Predicted deleterious variants in the human genome relevant to gene therapy with adeno-associated virus vectors - Mahboubeh R. Rostami; Philip L. Leopold; Jenifer M. Vasquez; Miguel de Mulder Rougvie; Alya Al Shakaki; Ali Ait Hssain; Amal Robay; Neil R. Hackett; Jason G. Mezey; Ronald G. Crystal (Molecular Therapy: Methods & Clinical Development, 2023)
Based on the observation that humans have variable responses of gene expression with the same dose of an adeno-associated vector, we hypothesized that there are deleterious variants in genes coding for processes required for adeno-associated virus (AAV)-mediated gene transfer/expression that may hamper or enhance the effectiveness of AAV-mediated gene therapy. To assess this hypothesis, we evaluated 69,442 whole genome sequences from three populations (European, African/African American, and Qatari) for predicted deleterious variants in 62 genes known to play a role in AAV-mediated gene transfer/expression. The analysis identified 5,564 potentially deleterious mutations of which 27 were classified as common based on an allele frequency ≥1% in at least one population studied. Many of these deleterious variants are predicated to prevent while others enhance effective AAV gene transfer/expression, and several are linked to known hereditary disorders. The data support the hypothesis that, like other drugs, human genetic variability contributes to the person-to-person effectiveness of AAV gene therapy and the screening for genetic variability should be considered as part of future clinical trials.